PtSn/γ-Al2O3 isobutane dehydrogenation catalysts: The effect of alkaline metals addition - Siri, Guillermo Jorge (2005)
In this work, the modifying effect of alkaline metals (Li, Na and K) is studied on the acid properties of the support and on the behavior of PtSn/γ-Al2O3 catalytic systems, in the isobutane dehydrogenation. The isopropyl alcohol transformation rate decreases sharply with the addition of alkaline metals, according to the sequence Li < Na < K. For the dehydrogenation reaction, the addition of K improves the stability level of the catalyst, and, as a result, PtSnK1.7 catalyst presents the best performance activity/selectivity/stability.